Losing one's mother: a journey through the Atlantic route of slavery - Lopes, Camila Souza [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
Amid railway development, a paradigm of progress and civilization, the government aimed to connect the left bank of the Tagus to the Algarve. Barreiro was chosen for its strategic location, due to its maritime accessibility and relatively close to Lisbon. It was from the implantation of the railroad that the installation of the industry was expected. The former region went from a small port linked to river fishing to a strong industrial zone, with demographic and urban expansion with more than half of the population working with industrial activity. In the mid-20th century, Barreiro was one of the largest industrial empires in the Iberian Peninsula. This article aims to discuss the transformation that developed in Barreiro as a result of the construction and industrial construction, as well as the construction of a local identity that is currently sought through entities and associations of local preservation.
Keywords: Railway; Industry; Barreiro town; Heritage; Conservation